The whisper apparatus - Kendall, Klayton Elliot, author; Morales, Juan, advisor; Taylor, Cynthia, committee member; Souder, Donna, committee member (Colorado State University. Libraries, 2011)
The Whisper Apparatus details the poet's lifelong withdrawal (and subsequent suffering) from the world of techne-logos to one of poiesis. The manuscript's tripartite structure corresponds directly to the poet's life and subtly depicts via occult motifs a journey inward and a return outward, a psycho-spiritual transformation occurring along the way. The Whisper Apparatus attempts, via the medium of verse, to speak the only linguistic alternative to techne-logos available to human beings on a dying planet: the language of witchcraft, the poetics of voodoo, the instructive "midwifery" of the pre-Socratic pagan philosophers. The poet offers an alternative to the misappropriation of Aristotelian mimesis by utilizing taxonomies of intuition, not scientific empiricism, by cataloging the subconscious via trance and dream. For the true sorcerer of words, Platonic anamnesis involves the logic of correspondence, not mathematical identity. The Whisper Apparatus, utilizing occult themes such as demonic possession and ritual drug use as a means of overcoming the psychotic symptoms and tendencies of a capitalist, patriarchal, and Puritanical upbringing, fits squarely in the Renaissance tradition of flirting with taboo, a transformation aesthetic employed by Sir Philip Sidney in Astrophil and Stella.